Antimicrobial Resistance: formulation of the response in the global health context - Silva, Rafael Almeida da (2020)
Antimicrobial Resistance (AMR) has proved to be a major public health problem at the global level. This paper examined the formulation of the response to AMR negotiated through the World Health Organization (WHO) by its Member States. Related WHO reports and resolutions from 1998 to 2019 were analysed. The findings indicate that, from 2014 on, more robust conditions were established for approval of a Global Action Plan on AMR, encompassing the concept of One Health and involving otherinternational entities (FAO, OIE, WTO and Unep). Content analysis and various analytical frameworks, considering two economic sectors (the livestock and pharmaceutical industries), proved relevant to illustrating the complexity of the issue, reinforcing its global importance and acknowledging the extent of antibiotic use in animals and the gaps in technological innovation. As the WHO is not only an important agent for mobilizing the response to AMR at the global level, but – despite a context of de-funding – has guaranteed a budget for action in this area, it is concluded that the public health perspective should prevail in the response to AMR.